126k views
3 votes
Simplify the expression.
a)1/64
b)2^-30
c)64
d)2^30

Simplify the expression. a)1/64 b)2^-30 c)64 d)2^30-example-1

2 Answers

9 votes


\left(((-1)^5)/((-2)^(-3)) \right)^2\\\\\\=\left((-1)/((1)/((-2)^3)) \right)^2\\\\\\=\left(-1 * -8\right)^2\\\\=8^2\\\\=64

User Steve Elmer
by
5.4k points
11 votes

Answer:


\huge\boxed{\bf\:64}

Explanation:


\left(((-1)^(5))/(\left(-2\right)^(-3))\right)^(2)

Now, simplify
(-1)^(5) = -1. Then,


\left((-1)/(\left(-2\right)^(-3))\right)^(2)

Calculate:
(-2)^(-3) = (1)/((-2)^(3)) = - (1)/(8).


\left((-1)/(-(1)/(8))\right)^(2)

Divide
-1 by
- (1)/(8). The result will be
8.


\left(-\left(-8\right)\right)^(2) \\= 8^(2)

Calculate
8 to its square which is
64.


8^(2)\\=\boxed{\bf\: 64} \: \:\mathrm{(3^(rd) \: option)}


\rule{150pt}{2pt}

Simplify the expression. a)1/64 b)2^-30 c)64 d)2^30-example-1
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.